UPAYA PENGADILAN DALAM PERLINDUNGAN HUKUM ANAK LUAR NIKAH BERDASARKAN SILA KE-5 PANCASILA - Dzanurusyamsyi Dzanurusyamsyi (Jurnal Pembaharuan Hukum, 2016)
In accordance with the Marriage Law Article 43 paragraph (1) and Article 100 Compilation of Islamic Law, that child out of wedlock obtain a civil relationship with her mother and her mother’s family. The provisions of article 43 paragraph (1) that the Court’s decision the Constitution of No. 046/PUU-VIII/2010 amended with the new norm, that “children born out of wedlock have links civil with her mother and her mother’s family as well as with men as a father to proven by science and technology and/ or other evidence under the law have blood relations, including civil relations with his father’s family’’ provisions of the new norm is still debatable and the pros and cons in the community that have not been finalized. Therefore, it is necessary to do research on: How Construction illegitimate child protection today; factors that affect the construction of the legal protection of a child out of wedlock is not justice at this time. This study used a qualitative approach with sosiolegal research. Factors that affect the protection of children out of wedlock is not justice due to several factors: -First; Factors Differing perceptions Ulama’ and Judges of children out of wedlock and protection against him; Factors Court decision is very diverse/ varied against illegitimate child protection issues; Factors diversity of perceptions on Registration of Population Administration in Indonesia. Then the provisions of the Marriage Law Article 43 paragraph (1)which has judicial review by the Constitutional Court Decision No. 046/PUU-VIII/2010 and Article 100 of the Compilation of Islamic Law must be reconstructed with the editor of a new article as follows: “a child born out of wedlock has relations civil with her mother and her mother’s family as well as with men as a father who can be proved by science and technology and/ or other evidence under the law have blood relation to the determination/ instruction judge and the Court’s decision, the Muslim Religious Court andbesides Islam in the District Court, including a civil relationship with his family “and there should be an affirmation form of additional chapters in the Marriage Law Article 43 with the editorial article as follows; “If it turns out according to a court ruling that the children who sought their origin was proven seedlings men and women and was born in/ from the marriage valid, then the child becomes legitimate child and have a relationship of civil full and relationships biological children with both parents and get inheritance rights.